Pengaruh Kesejahteraan Karyawan, Motivasi, Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Pos Indonesia Cabang Probolinggo - Izzatul Afkarina; R Abdul Haris; Mutinda Teguh Widayanto (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The main objective of human resource management is to increase the contribution of human resource management (employees) to organizations/institutions in order to achieve organizational goals. The independent variables consist of employee welfare, motivation, and work discipline while the dependent variable is employee performance. The population in this study were employees of PT Pos Indonesia Probolinggo Branch. The sampling technique in this study used a non-probability sampling technique, namely saturated sampling. Sources of data used in this study are primary data and secondary data. Processed using data analysis in the form of validity and reliability tests, classic assumption tests (normality test, heteroscedasticity test, multicollinearity test), multiple linear regression analysis, coefficient of determination, and hypothesis testing (t test). The results of this study indicate that: employee welfare, motivation, and work discipline have a significant effect on employee performance at PT Pos Indonesia Probolinggo Branch.